PSYCHOEMOTIONAL ATTITUDES AS A MEANS OF STRENGTHENING MENTAL HEALTH JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2022)
The author proves that in primary school students through their experiences failures and successes are formed corresponding range of emotions. Strictly positive emotions, stimulate a cheerfl mood practice primary schoolchildren, and this helps to improve their mental health.
Keywords: attitudes; harmonious development; health; primary school students; postive feelings; emotional openes